Beryllium-10 measurements from Jakobshavn Isbræ, 2018 - Allie Balter-Kennedy; Nicolás Young; Jason Briner; Brandon Graham; Joerg Schaefer (Arctic Data Center, 2021)
Erosion beneath glaciers and ice sheets is a fundamental Earth-surface process dictating landscape development, which in turn influences ice-flow dynamics and the climate sensitivity of ice masses. The rate at which subglacial erosion takes place, however, is notoriously difficult to observe because it occurs beneath modern glaciers in a largely inaccessible environment. The data presented here are 31 Beryllium-10 (Be-10) measurements from bedrock surfaces near Jakobshavn Isbræ, western Greenland, collected in August 2018, that we use to calculate exposure ages and subglacial erosion rates for the period of historical ice cover. Also included are 17 Be-10 measurements in a 4-meter (m)-long bedrock core, taken within the same landscape, that we use to constrain subglacial erosion rates on centennial and orbital timescales. Here we provide all input data needed to independently calculate Be-10 ages or erosion rates, including the associated lab-blank dataset.